Correction to: Repeated praziquantel treatment and Opisthorchis viverrini infection: a population-based cross-sectional study in northeast Thailand - Kavin Thinkhamrop; Narong Khuntikeo; Paiboon Sithithaworn; Wilaiphorn Thinkhamrop; Kinley Wangdi; Matthew J. Kelly; Apiporn T. Suwannatrai; Darren J. Gray (BMC, 2019)
In the original publication of this article [1], there is an error in the section of 'Ethics approval and consent to participate' at the end of the article, the correct Ethics reference number should be HE551404 rather than HE591067.